A PROSPECTIVE STUDY OF ADVERSE DRUG REACTIONS IN A TERTIARY CARE HOSPITAL IN SOUTH INDIA - JERIN JAMES; JAMUNA RANI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of this study was to determine the prevalence of adverse drug reactions (ADRs) in a tertiary care teaching hospital in South India and to analyze the causality according to the Naranjo scale. Methods: This study was carried out at the SRM Medical College, Chennai, a tertiary care hospital, which is an ADR monitoring center under Pharmacovigilance Programme of India, over a period of 1 year, from September 2017 to August 2018, after approval by the Institutional Ethics Committee. These ADRs were reported by the clinical pharmacy team of our hospital to the department of pharmacology. The relevant data were collected from the patient case notes, treatment charts, laboratory data reports, ADR notification forms, patient interview, and reporter interviews after written informed consent was obtained from each patient. Patients of either sex of all ages who developed ADR within the hospital were included in the study. Patients who developed ADR outside the hospital were excluded from the study. The collected ADRs were subjected to the Naranjo causality assessment scale. Hartwig’s scale was used to assess the severity of the reaction. The causalities and other aspects of the ADRs were analyzed in detail. Results: A total of 80 ADRs were reported during this study period. The ADRs were most frequently reported in the adult age group (75%) with slight female preponderance (60%). Antibiotics contributed to the maximum number of ADRs which accounted for 52.5% of the total, of which beta-lactams were the highest (37.5%) followed by analgesics. Causality assessment of ADRs by the Naranjo scale showed that the maximum reactions could be categorized as probable (85%) followed by the possible category (15%). The most common presentation of ADR was itching (45%) followed by rashes (30%). Three cases of severe adverse reactions were reported, one case each of anaphylaxis to pantoprazole and diclofenac and one case of Steven–Johnson syndrome to cotrimoxazole. Conclusion: ADRs are a common occurrence but are often not recognized. Even if recognized, they are underreported as many physicians are unaware that all ADRs should be reported to ADR monitoring centers. ADRs are an important cause of morbidity and mortality all over the world and are an important public health concern. It inflicts a negative impact on the treatment and exerts a greater economic burden on the patient if it results in prolongation of the duration of hospitalization or other comorbidities. Therefore, the practicing physicians, as well as the nursing staff, should be sensitized of the importance of ADR reporting to their respective pharmacovigilance centers.